Experimental Studies on Efficacy of Dexmeditomidine and Magnesium as Adjuncts to Epidural Bupivacaine for Upper Abdominal Surgeries - Tantry Tariq Gani; Abdul Waheed Mir; Mohamad Akbar Shah; Farooq Ahmad Ganie; Shazia Naz; Mohd Iqbal Dar (Technological Innovation in Pharmaceutical Research Vol. 8, 2021)
Background: The goal of this prospective, randomised, double-blind research was to see how adding magnesium or dexmedetomidine to epidural bupivacaine in upper abdomen procedures affected the outcome. Materials and Methods: Sixty ASA (American Society of Anesthesiologists) class I and II patients undergoing upper abdominal procedures were randomly assigned to either magnesium sulphate (Group M) or dexmedetomidine (Group D) as well as epidural bupivacaine for surgical anaesthesia. All of the trial participants were given an epidural anaesthetic with 8 ml of 0.5 percent bupivacaine and either 50 mg MgSO4 (Group M) or 1 g/kg dexmedetomidine (Group D). Duration of analgesia, total rescue analgesic requirement, hemodynamic parameters and any adverse events were monitored. Results: Analgesia in the postoperative phase was better in Group BD, as was the need for rescue analgesics. Sedation was more common in Group BD. Conclusion: Dexmeditomidine prolongs the duration of analgesia and produces significant sedation. As a result, combining dexemedetomidine with epidural bupivacaine may provide greater analgesia and arousable sedation.